A realist review of one‐to‐one breastfeeding peer support experiments conducted in developed country settings. Issue 1 (6th December 2017) - Trickey, Heather; Thomson, Gill; Grant, Aimee; Sanders, Julia; Mann, Mala; Murphy, Simon; Paranjothy, Shantini
Abstract: The World Health Organisation guidance recommends breastfeeding peer support (BFPS) as part of a strategy to improve breastfeeding rates. In the UK, BFPS is supported by National Institute for Health and Care Excellence guidance and a variety of models are in use. The experimental evidence for BFPS in developed countries is mixed and traditional methods of systematic review are ill‐equipped to explore heterogeneity, complexity, and context influences on effectiveness. This review aimed to enhance learning from the experimental evidence base for one‐to‐one BFPS intervention. Principles of realist review were applied to intervention case studies associated with published experimental studies. The review aimed (a) to explore heterogeneity in theoretical underpinnings and intervention design for one‐to‐one BFPS intervention; (b) inform design decisions by identifying transferable lessons developed from cross‐case comparison of context‐mechanism‐outcome relationships; and (c) inform evaluation design by identifying context‐mechanism‐outcome relationships associated with experimental conditions. Findings highlighted poor attention to intervention theory and considerable heterogeneity in BFPS intervention design. Transferable mid‐range theories to inform design emerged, which could be grouped into seven categories: (a) congruence with local infant feeding norms, (b) integration with the existing system of health care, (c) overcoming practical and emotional barriers to access, (d) ensuring friendly, competent, and proactive peers, (e) facilitating authentic peer–mother interactions, (f) motivating peers to ensure positive within‐intervention amplification, and (g) ensuring positive legacy and maintenance of gains. There is a need to integrate realist principles into evaluation design to improve our understanding of what forms of BFPS work, for whom and under what circumstances.